Sporadic renal hybrid oncocytic/chromophobe tumor in a young man: A case report. Issue 33 (August 2019) - Hou, Bingbing; Liang, Chaozhao
Abstract: Rationale: Hybrid oncocytic/chromophobe tumor (HOCT) is defined as tumor composed of renal oncocytoma (RO) and chromophobe renal cell carcinoma (CHRCC). Sporadic HOCT is extremely rare, the preoperative diagnosis is difficult, and no guidelines for clinical therapy. We report a case who is the youngest male patient of sporadic HOCT in the world, review the previously reported cases, and share the clinical features, diagnosis, treatment, and prognosis of HOCT. Patient concerns: A 30-year-old man was admitted with the complaints of incidental right renal tumor detected by abdominal ultrasound. He had no complaints of urological symptoms, abdominal pain, osphyalgia, and hematuria. Abdominal contrast-enhanced computed tomography revealed an 85 mm × 80 mm × 80 mm unilateral and solid renal mass, and no findings of metastases. Diagnosis: The preoperative diagnosis was right renal tumor. Interventions: Laparoscopic right radical nephrectomy was performed. Outcomes: Histopathology demonstrated a mixture of cells with the morphologic features of those seen in CHRCC and RO. The patient was final diagnosed as sporadic HOCT. After follow-up of 14 months, the patient had no complaints and evidence of disease recurrence. Lessons: Sporadic HOCT is extremely rare. It is possible that core biopsy could improve diagnostic accuracy. Laparoscopic radical nephrectomy or nephron sparing surgery should be considered the clinical therapy of the sporadic HOCT patients. The clinical behavior of HOCT is still entirely uncertain and should be proved by studies with available long follow-up.